IMPLEMENTASI PERATURAN BUPATI NOMOR 50 TAHUN 2013 TENTANG DANA KESEJAHTERAAN NELAYAN DI KABUPATEN PATI - Naufan Redha Setyaji; Ahmad Taufiq; Sulistyowati . (Journal of Politic and Government Studies, 2016)
This study aimed to find out the implementation of the Regent Decree 50/2013on the fishermen welfare fund in Pati Regency. TheMunicipal Office of MaritimeAffairs and Fisheries of Pati Regency became the most influential institution in theimplementation of the decree.This study using implementation theory of Donald S.Van Meter and Carl E. Van Horn, especially the factors affected the implementationof a program.The study applied a qualitative approach and a descriptive researchmethod. Research data were collected by interview with concerned respondents. Therespondents from the government institution consisted of those with capacity andauthority dealing with the implementation of the Regent Decree 50/2013. Whereas,the respondents outside the government institutions were selected from leaders offishermen collective unit (KUB) as the performing agents on at the lower tiers.The study found that the implementation of the Regent Decree 50/2013 on thefishermen welfare fund in Pati Regency was still overshadowed by multipleproblems, such as invalid data recording, which led to funding misallocation. Thismisallocated funding had cause improper distribution where many fishermen did notget the fund they needed. In addition, the study also found that the amount of thefunding was inadequate to fulfill the need during bad season.